2022
DOI: 10.1177/09673911221133438
|View full text |Cite
|
Sign up to set email alerts
|

The effect of silica and copper nanoparticles in polyimide on the friction and wear of polyethersulfone/polyimide mixture

Abstract: The synergistic effect of silica (SiO2) and copper (Cu) nanoparticles in polyimide (PI) on the friction interfacial deformation of polyethersulfone/polyimide (PES/PI) blends was studied. Results indicate that the effect of SiO2 and Cu nanoparticles on the tribological performance of PES/PI nanocomposites is quite different from each other. The addition of SiO2 nanoparticles into PI improves the antifriction of PES/PI nanocomposites by 24.4%, but has little effect on the wear resistance. The incorporation of Cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…65 Subsequently, the polyimide nanocomposite films own superior physical properties, relative to neat polyimide films. [66][67][68] In this respect, nanocarbon nanofillers have been filled in the polyimide films. [69][70][71] The polyimide/carbon nanotube nanocomposite films have been developed.…”
Section: Polyimide/fullerene Nanocomposite Filmsmentioning
confidence: 99%
“…65 Subsequently, the polyimide nanocomposite films own superior physical properties, relative to neat polyimide films. [66][67][68] In this respect, nanocarbon nanofillers have been filled in the polyimide films. [69][70][71] The polyimide/carbon nanotube nanocomposite films have been developed.…”
Section: Polyimide/fullerene Nanocomposite Filmsmentioning
confidence: 99%
“…The researchers speculated that Cu nanoparticles can enhance the tribological properties of the grease by serving as nano-bearings, forming an additional lubricating film when melted and deposited on the rubbing surface. In research by, Zhou et al, 43 the tribological properties of silica (SiO 2 ) and copper (Cu) nanoparticles added to a polymer mixture of polyethersulfone/polyimide (PES/PI) are evaluated by using a reciprocating ball-on-disc friction and wear tester. Their results showed that PES/PI with SiO 2 nanoparticles had a 24.4% reduction in COF and a 6.1% decrease in wear rate.…”
Section: Introductionmentioning
confidence: 99%